Paul Gauguin Un esotismo controverso - MESSINA, MARIA GRAZIA (Studi e saggi, 2006)
Gauguin's exoticism, an inexhaustible source of mythical constructions, is subjected to a careful revision of the contemporary, complex interference between symbolist culture and the pressures of colonial policies. Different perspectives are adopted, from the analysis of the theme of the mask in self-portraits, to literary suggestions, to suggestions received from the Universal Exposition of 1889, up to a reinterpretation of the stays in Brittany and Oceania, intended to clarify the links between exoticism and nostalgia, in a definition of escaping into space as the substitute for a regression of time, in search of a dimension of the origins now precluded to modern people.